2007
DOI: 10.1021/jf0718648
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation of Endosulfan in Field-Grown Tomato (Lycopersicon esculentum) and Cropped Soil at Akumadan, Ghana

Abstract: The dissipation and persistence of endosulfan (6,7,8,9,10,10-hexachloro-1,5,5a,6,9,9a-hexahydro-6,9-methano-2,4,3-benzodioxathiepin 3-oxide) applied to field-grown tomato (Lycopersicon esculentum) were studied at a vegetable-growing location in Ghana. Plant tissue samples and cropped soil collected at 2 h-14 days and 8 h-112 days, respectively, after application, were analyzed by gas chromatography-electron capture detection (63Ni) to determine the content and dissipation rate of endosulfan isomers (alpha- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 30 publications
4
16
1
1
Order By: Relevance
“…The percentage dissipation was 71.64% for ∑endosulfan, while parent isomers α-and βisomers were 70.58% and 80.24%, respectively. These values agreed with the dissipation of endosulfan from foliar part of cotton (Kennedy et al, 2001) and tomato plants (Ntow et al, 2007) after 7 days of treatment. The National Research Council, Canada (NRC) reported that in most fruits and vegetables, 50% of the parent residue is lost within 3 to 7 days after application (NRC, 1975).…”
Section: Theobroma Cacao Vegetationsupporting
confidence: 83%
See 3 more Smart Citations
“…The percentage dissipation was 71.64% for ∑endosulfan, while parent isomers α-and βisomers were 70.58% and 80.24%, respectively. These values agreed with the dissipation of endosulfan from foliar part of cotton (Kennedy et al, 2001) and tomato plants (Ntow et al, 2007) after 7 days of treatment. The National Research Council, Canada (NRC) reported that in most fruits and vegetables, 50% of the parent residue is lost within 3 to 7 days after application (NRC, 1975).…”
Section: Theobroma Cacao Vegetationsupporting
confidence: 83%
“…The half-life values obtained in this study for Theobroma cacao vegetation (fresh foliar, stem bark and cocoa pods) were significantly higher than values reported in field grown tomato (Lycopersicon esculentum L) at Akumadan, Ghana (Ntow et al, 2007) and eggplant (Solanum macrocarpon L.) grown in Southern Benin, West Africa (Rosendahl et al, 2009). The wide difference may be due mainly to their morphological differences, for example, wider surface leaf laminar, canopy and greater waxy leaf cuticle in Theobroma cacao, cultivation practice and as well as higher dose concentration for crop treatment -all of these are likely to favour higher foliar half-life in Theobroma cacao.…”
Section: Kinetic Variables For Vegetationcontrasting
confidence: 77%
See 2 more Smart Citations
“…由于α-硫丹和 β-硫丹具有不同的物理化学性质, 因而导致其在环境 介质中的行为存在较大的差异. 研究表面, 相比于α-硫 丹, β-硫丹的毒性偏小 [47] , 但其在沉积物中具有更长的 持久性和更高的渗透速率 [48] . 我国对东部边缘海沉积 物中硫丹的环境行为研究较少, 目前主要集中在长江 口及其附近的东海内陆架地区.…”
Section: Ocpsunclassified